Implementasi Akad Wadiah Pada Produk Tabungan Faedah Pada PT. Bank Syariah Indonesia Kcp Binjai - Rania Ghassani; Muhammad Saleh; Sri Wahyuni Hasibuan (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This research was conducted to determine the implementation of wadi'ah contracts on benefit savings products at Bank Syariah Indonesia KCP Binjai, the mechanism for giving gifts to benefit savings products at Bank Syariah Indonesia KCP Binjai and the suitability of benefit savings products with the Fatwa of the National Sharia Council. In this study using a type of field research with a qualitative research approach.  The methods used in this study are observation, interviews and documentation. The results showed that the benefit savings applied at Bank Syariah Indonesia KCP Binjai were appropriate, namely using wadi'ah yad dhamanah contracts and were in accordance with the Fatwa of the National Sharia Council. The mechanism for awarding bonuses is in accordance with the DSN Fatwa, namely the amount to be received is not delivered at the beginning of the contract. It's just that the voluntary bonus in the DSN Fatwa mentioned that the bonus must be given in the form of goods / services, but in practice at Bank Syariah Indonesia KCP Binjai bonuses are given in the form of nominals that go directly to the customer's account.